The construction and effectiveness of offensive plays in basketball by using systematic observation - Fernandez, J.; Camerino, O.; Anguera, M. T.; Gibert, A.; Jonsson, G. K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In the field of sports research there is a growing need for the rigorous collection of data that provide empirical evidence about the complex reality they refer to. Key aspects in this regard include the presence of regularities that are not detectable through visual inference or traditional methods of data analysis, the lack of standard observation instruments and the priority need to develop powerful, computerized coding systems, all of which must form part of an approach that is suitable for natural and habitual contexts (Morris & Burwitz, 1989). Method: The observational methodology used had the rigor and flexibility needed to study the episodes and different configurations of play just as they occurred. Ten ACB basketball games (First Spanish Division) were recorded and the instrument used was the Match Vision Studio software (Perea, Alday & Castellano, 2004), which has enabled us to set up code and category of the situation space of the players in the two previous moves to the basket. The approach here concerns the way in which temporal patterns are able to reveal those aspects of social interaction that are not immediately observable, and considers that every interactive flow is governed by behavioural structures of varying stability that can be visualized by detecting hidden temporal patterns such as T-patterns. These temporal patterns can be detected by means of the powerful algorithm of the THEME software, developed by Magnusson (1996). Results: A total of 3478 T-patterns were detected in the subset of games won. Given the temporal patterns detected and the results obtained in the lag sequential analysis we then turned our attention to those co-occurrences in which there was a disparity according to game performance. Discussion: The results show that it is possible to identify stable spatial structures that provide information about areas and positions of players more effective in launching basket and an imbalance that provide more effective for completion and the type of termination of attack that can be applied for the improvement of sports training and initiation. The selection of the data has been grouped into different criteria.